Supplier development Practices in the South African Motor Industry - Bayne, Lyndie (GSB: Faculty, 2014)
The purpose of this dissertation was to determine the nature and extent of supplier development policy, strategy and practices in the South African (SA) motor industry. This fills a gap in the SA motor industry literature by focusing exclusively and comprehensively on the topic of supplier development. Multiple data sources and methods were used to gain a balanced, holistic perspective of supplier development in the industry. The perspectives of both the Original Equipment Manufacturers (OEMs) and a sample of key first-tier suppliers were obtained. This provides a dyadic study of supplier development, which is a rarity in the international supplier development literature. The views of other organisations playing a role in supplier development in the SA motor industry were sought to provide further insight. Survey data was obtained from the whole population of light passenger vehicle OEMs located in SA. This contributes comprehensive empirical data to the international supplier development research, which is predominantly case-study based. The supplier development practised by the OEMs with respect to first- and second-tier suppliers was investigated, as well as that employed by first-tier suppliers with respect to second-tier suppliers. In addition to providing an overview of supplier development in the SA motor industry as a whole, further insight is provided by a mini case study of an OEM exhibiting best practice in supplier development. OEMs and first-tier suppliers differ in their perspectives regarding the overall level of supplier development practised by the OEMs. OEMs consider the level of supplier development they provide to be high to moderate, while the first-tier suppliers perceive the supplier development received to be moderate to low. However, the research suggests that vi the level of supplier development practised by the OEMs in the SA motor industry is nevertheless likely to be more intense than that enjoyed by suppliers in most other SA industries. The level of supplier development employed by OEMs was found to be cyclical, peaking at times of new model / part introductions, thereafter moving from proactive to reactive in nature. A key finding was that the overwhelming majority of first-tier suppliers regard Toyota South Africa Motors (Pty) Ltd to be the leader in supplier development in SA. Another interesting finding was that the significant East versus West distinction found in the international supplier development literature is not applicable to the SA situation. Rather, in SA, the relevant division is between Toyota and the other SA OEMs. When sourcing locally, the OEMs prefer to source components from global first-tier suppliers situated in SA. These include SA subsidiaries of global companies, SA suppliers with foreign joint venture partners or SA suppliers with foreign technical agreement partners. The research revealed that many local first-tier suppliers believe that they receive more developmental support from their foreign head-offices or foreign partners, than from the SA OEMs. The OEMs and first-tier suppliers rarely develop foreign suppliers, who supply a significant proportion of total component requirements. The development of foreign suppliers is left to the OEM and first-tier counterparts in the foreign countries. The development of second-tier suppliers in SA is considered to be the responsibility of the first-tier suppliers, with OEMs seldom getting involved. The local first-tier suppliers engage in moderate to low supplier development with respect to local second-tier suppliers, citing a lack of resources as the primary reason. Global competition, the Motor Industry Development Plan (MIDP) and Broad-Based Black Economic Empowerment (B-BBEE) are identified as key drivers of the OEMs' supplier vii development strategy in SA. There is renewed pressure being placed on the OEMs to improve their sourcing of components from B-BBEE companies. This is in turn resulting in increased pressure being placed on first-tier suppliers to improve their B-BBEE scorecards. Although most OEMs have specific supplier development policies relating to B-BBEE, and government and others have implemented initiatives to develop these suppliers, the amount of component sourcing from such companies was found to be low. The research highlighted innovative projects and institutions playing a role in supplier development in SA, such as the Durban Auto Cluster and The South African Auto Benchmarking Club. The multi-source data obtained in this dissertation provides an empirical benchmark against which to measure the success of future supplier development initiatives. The dissertation also allows industry players to identify how their supplier development policies, strategy and practices compare to the industry as a whole, as well as to best practice.